Road to the restoration of the Ohrid Archbishopric - Borisov Dejan, Борисов Дејан (George Fox University, 2017)
The restoration of the abolished Ohrid Archbishopric did not begin with the processes at the end of the World War II, but immediately after its abolition in the eighteenth century. The restoration of the Ohrid Archbishopric as the Macedonian Orthodox Church is in full accordance with the church tradition and practices established by the other local Orthodox churches in the process of obtaining their autocephaly during the nineteenth and twentieth centuries.
Issue 4, Special Issue on the Fiftieth Anniversary of the Declaration of the Autocephaly of the Macedonian Orthodox Church
Keywords: Ohrid Archbishopric, Metropolitan Theodosius (Gologanov), Bulgarian Exarchate, Constantinople Patriarchate, Autocephalous United Orthodox Church of the Kingdom of Serbs, Croats and Slovenes, autocephaly.